2020
DOI: 10.2217/fmb-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pharmaceutical Nanotechnology in the Time of COVID-19 Pandemic

Abstract: There is no effective therapy against COVID-19 available so far. In the last months, different drugs have been tested as potential treatments for COVID-19, exhibiting high toxicity and low efficacy. Therefore, nanotechnology can be applied to improve the therapeutic action and minimize the toxicity of loaded drugs. In this review, we summarized the drugs tested as COVID-19 treatment and the advantages of antiviral nanostructured drug-delivery systems. Such systems have demonstrated low in vitro toxicity with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 94 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…In light of the current COVID-19 pandemic, the plethora of studies on the disease pathogenesis and development of therapeutic and preventive options, there are unexplored areas such as repurposing and reformulating currently available antivirals, especially as nano-formulations. Many researchers have suggested that curcumin may play a prominent role in COVID-19 therapy [ [105] , [106] , [107] ]. A safe NE formulation with antiviral oil, antiviral surfactant/cosurfactant, and antiviral drugs/substances may provide a promising solution for COVID-19 therapy.…”
Section: Future Scopementioning
confidence: 99%
“…In light of the current COVID-19 pandemic, the plethora of studies on the disease pathogenesis and development of therapeutic and preventive options, there are unexplored areas such as repurposing and reformulating currently available antivirals, especially as nano-formulations. Many researchers have suggested that curcumin may play a prominent role in COVID-19 therapy [ [105] , [106] , [107] ]. A safe NE formulation with antiviral oil, antiviral surfactant/cosurfactant, and antiviral drugs/substances may provide a promising solution for COVID-19 therapy.…”
Section: Future Scopementioning
confidence: 99%
“…(II) Inside host cells, favipiravir carried by the nano-emulsion can interfere with the actions of the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp). 171 …”
Section: Proposed Action Mechanismmentioning
confidence: 99%
“…VLPs of Macrobrachium rosenbergii nodavirus (MrNVLPs) have been developed as a multifunctional drug delivery vehicle, whereas folic acid was chemically conjugated to the surface exposed lysine amino acid, while doxorubicin was internally loaded within the MrNVLPs via infusion approach. Authors reported sustained DOX release in a thermally responsive manner with an increase in drug release in response to an elevated temperature of 43°C on HT29 cells than CCD841CoN normal cells while reducing DOX cytotoxicity on the normal cells as they lack the overexpression of folate receptor [ 133 , 134 ].…”
Section: Viruses As Drug Carriersmentioning
confidence: 99%